A Novel Pyroptosis-Based Prognostic Model Correlated with the Parainflammatory Immune Microenvironment of Pancreatic Cancer - Kong-kong Wei; Zhi-xing Du; Jun-ge Deng; Jin-wei Yang; Hao Chen (Journal of Immunology Research)
Background. Pyroptosis has a dual function in malignant tumor progression and management. The action of pyroptosis-related genes (PRGs) in pancreatic cancer (PC), however, remains uncertain. Methods. Differential expression analyses of 57 PRGs were conducted in the TCGA TARGET GTEx dataset. The candidate genes were determined using LASSO Cox regression and random forest analyses. A risk model was developed with the TCGA dataset and validated with the ICGC dataset. Results. Three prognosis-related PRGs (BAK1, GSDMC, and IL18) were chosen to create a risk model. High-risk patients from the TCGA and ICGC cohorts had an unfavorable overall survival (all p<0.05). The risk modelʼs accuracy and independent predictability were assessed by receiver operating characteristic curves and multivariate Cox regression analysis, respectively. High-risk patients possessed different molecular pathways, higher KRAS and TP53 mutations, increased expression of PD-L1, C1 immune subtype, and immunosuppressive microenvironment characterized by parainflammation compared to low-risk patients. KRAS and TP53 mutations participated in different inflammatory pathways and played different prognostic roles between the two risk groups. KRAS mutations in high-risk patients caused a more unfavorable prognosis than wild-type KRAS (p=0.016), whereas TP53 mutations in low-risk patients exhibited a poorer outcome than wild-type TP53 (p=0.009). Spearman correlation analyses revealed that the parainflammatory response in PC might be implicated in GSDMC-mediated pyroptosis via cytosolic DNA-sensing pathways under hypoxic conditions. Furthermore, the risk scores were significantly and positively related to the expression of HNRNPC, RBM15, YTHDF1, and YTHDF2, as well as sensitivity to gemcitabine, cisplatin, and erlotinib. Conclusions. This study created a novel pyroptosis-based risk model related to the parainflammatory immune microenvironment, which might help identify novel biomarkers, evaluate the tumor immune microenvironment, and develop management strategies for PC patients.